Continuous glucose monitoring for hypoglycemia and diabetic ketoacidosis risk reduction among diabetic patient using insulin: A literature review - Rohmah, Assyfa Siti; Herawati, Tuti (Holistik Jurnal Kesehatan, 2024)
Background: Hypoglycemia and diabetic ketoacidosis (DKA) are the two most common complications in diabetes patients. Monitoring blood glucose levels to prevent acute complications is an important part of diabetes management. In the era of increasingly advanced technology, technology can be used to monitor blood glucose, namely continuous glucose monitoring (CGM).Purpose: To provide an overview of the effectiveness of using CGM devices as diabetes management to reduce the incidence of hypoglycemia and DKA in diabetes patients receiving insulin therapy.Method: Literature review research to identify through a database all articles related to the topic of the effectiveness of continuous glucose monitoring (CGM). Literature search using boolean search with population "Diabetes Type 1" OR "Diabetes Patients" OR "Diabetes Type II", Intervention "Flash Glucose Monitoring" OR "Continuous Glucose Monitoring" OR "Real Time Glucose Monitoring", and outcome: "Hypoglycemia" OR “Diabetic Ketoacidosis” OR “Complications” OR “Diabetes Management”.Results: Identified 360,710 articles and found 15 suitable articles, of which 7 articles discussed that CGM can reduce the incidence of hypoglycemia, 7 articles discussed that CGM installation was related to reducing HbA1C, and 2 articles proved that CGM was related to reducing the incidence of DKA.Conclusion: The use of CGM effectively and efficiently helps nurses in monitoring blood glucose levels while in the inpatient room in the management of diabetes patients so that it is easier to detect the possibility of hypoglycemia and prevent DKA due to ongoing hyperglycemia.Suggestion: It is hoped that further research can compare the effectiveness of using CGM equipment based on various types or models. Keywords: Blood Glucose Monitoring; Continuous Glucose Monitoring; Diabetic Ketoacidosis; Hyperglycemia. Pendahuluan: Hipoglikemia dan diabetic ketoacidosis (DKA) merupakan dua komplikasi paling sering terjadi pada pasien diabetes. Pemantauan kadar glukosa darah sebagai pencegahan komplikasi akut menjadi bagian penting dalam manajemen diabetes. Di era teknologi yang semakin maju, penggunaan teknologi dapat digunakan sebagai pemantauan glukosa darah yaitu continuous glucose monitoring (CGM).Tujuan: Untuk memberikan gambaran efektivitas penggunaan alat CGM sebagai manajemen diabetes untuk menurunkan kejadian hipoglikemia dan DKA pada pasien diabetes yang mendapat terapi insulin.Metode: Penelitian literature review untuk melakukan identifikasi melalui basis data dari semua artikel berkaitan dengan topik efektivitas continuous glucose monitoring (CGM). Pencarian literatur menggunakan boolean search dengan population “Diabetes Type 1” OR “Diabetes Patient” OR “Diabetes Type II”, Intervention “Flash Glucose Monitoring” OR “Continuous Glucose Monitoring” OR “Real Time Glucose Monitoring”, dan outcome: “Hypoglycemia” OR “Diabetic Ketoacidosis” OR “Complications” OR “Diabetes Management”.Hasil: Mengidentifikasi sebanyak  360.710 artikel dan mendapatkan 15 artikel yang sesuai dimana 7 artikel membahas CGM dapat menurunkan kejadian hipoglikemia, 7 artikel membahas pemasangan CGM berkaitan dengan penurunan HbA1C, dan 2 artikel membuktikan CGM berkaitan dengan penurunan kejadian DKA.Simpulan: Penggunaan CGM efektif dan efisien membantu perawat dalam melakukan pemantauan kadar glukosa darah selama di ruang rawat inap dalam manajemen penanganan pasien diabetes sehingga lebih mudah dalam mendeteksi kemungkinan terjadinya hipoglikemia dan pencegahan DKA akibat hiperglikemia berkelanjutan.Saran: Diharapkan penelitian selanjutnya dapat membandingkan efektivitas penggunaan alat CGM berdasarkan dari berbagai jenis atau modelnya. Kata Kunci: Continuous Glucose Monitoring; Diabetic Ketoacidosis; Hiperglikemia; Pemantauan Glukosa Darah.